2011
DOI: 10.1177/0960327111426585
|View full text |Cite
|
Sign up to set email alerts
|

Influence of flavonoid extracts from celery on oxidative stress induced by dichlorvos in rats

Abstract: The present work was to investigate the effects of flavonoid extracts from celery on oxidative stress induced by dichlorvos (DIC) in male Wistar rats maintained on a normal diet. The rats were given DIC through intragastric administration by the dose of 7.2 mg/kg·body weight (bw)/day and additionally added 5% flavonoid extracts to the diet for 4 weeks continuously. The activities of superoxide dismutase (SOD), glutathione peroxidase (GPx), catalase (CAT), glutathione-S-transferase (GST) and the content of malo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…They possess several biological and pharmacological properties that have made them useful as therapeutic agents against chemical-induced toxicity, among others. Several studies have shown flavonoids with the potential to protect against pesticide-induced toxicities [23, 24]. Epicatechin (EC) is a flavan-3-ol, a sub-class of the flavonoids found in green tea, grape, and cocoa [25].…”
Section: Introductionmentioning
confidence: 99%
“…They possess several biological and pharmacological properties that have made them useful as therapeutic agents against chemical-induced toxicity, among others. Several studies have shown flavonoids with the potential to protect against pesticide-induced toxicities [23, 24]. Epicatechin (EC) is a flavan-3-ol, a sub-class of the flavonoids found in green tea, grape, and cocoa [25].…”
Section: Introductionmentioning
confidence: 99%
“…Mosse et al have shown that winery wastewater delayed germination and inhibited vegetative growth of several plants. We have studied and shown variations of oxidative stress in bean leaves exposed to pesticides and grape marc, measuring transcript accumulations of stress gene markers, such as superoxide dismutases, catalase, ascorbate peroxidase, ubiquitin, and hsp 70, as previously described. Agati et al recently proposed a model in which chloroplast-located flavonoids scavenge generated ROS, thus avoiding programmed cell death. They suggested that flavonoids in conjunction with peroxidases and ascorbic acid constitute a secondary antioxidant system.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Qian states that the flavonoid components in plants can provide benefits in improving vascular endothelial cell function in NO bioavability disorders due to glucotoxic conditions. (11) Sulforaphane as an inductor of Nrf2 has the ability to react with sulfhydryl (-SH) and Nrf2 groups bound to sulfur compounds. SFN can prevent Ang II-induced cardiomyopathy through Nrf2-mediated activation of exogenous antioxidant defenses, and regulation and activation of Nrf2 by SFN through the Akt / GSK-3β / Fyn pathway.…”
Section: Discussionmentioning
confidence: 99%